Germinated Cempo Ireng Black Rice (Oryza sativa L.) Demonstrates Functional Anti-Obesity Effects in High-Fat Diet-Induced Rats - Salamah, Mina Parhatus; Mayangsari, Yunika; Shirakawa, Hitoshi; Agista, Afifah Zahra; Saputra, Wahyu Dwi (Trends in Sciences, 2026)
Obesity is a long-term metabolic disorder caused by an imbalance between energy consumption and energy expenditure, leading to excessive fat accumulation. This condition is closely associated with metabolic disorders, thus requiring effective strategies for prevention and management. One such approach is the consumption of functional foods, such as whole grains like black rice, whose functional value can be enhanced through germination. This study aimed to evaluate the effects of administering germinated black rice (GBR) to rats with a high-fat diet (HFD), compared with non-germinated black rice (NGBR) and white rice (WR). The results showed that GBR significantly suppressed body weight gain, liver mass, and adipose tissue mass, approaching levels observed in the control group. GBR also improved lipid profiles by reducing total cholesterol, triglycerides, and LDL, while increasing HDL and cecal cholesterol excretion. The most significant reduction in blood glucose levels was observed in the GBR group (Δ −49 mg/dL), accompanied by a decrease in hepatic malondialdehyde levels, indicating a reduction in oxidative stress. Additionally, GBR increased the concentrations of acetate, propionate, and butyrate, which contribute to metabolic improvement. Histopathological analysis revealed smaller adipocyte size and reduced hepatic steatosis in the GBR group. Gene expression analysis revealed significant downregulation of Hmgcr, suggesting an inhibition of hepatic cholesterol biosynthesis. These results indicate that germinated black rice exerts stronger anti-obesity effects than NGBR and WR, supporting its potential as a functional food for obesity prevention. HIGHLIGHTS Germinated black rice Cempo Ireng variety was evaluated for its anti-obesity potential in HFD rats. A rodent obesity model was used to assess metabolic and gene-expression changes. Germinated black rice Cempo Ireng variety significantly reduced adiposity and improved lipid profiles. Improved lipid metabolism was linked to downregulation of Hmgcr and Fasn Findings support germinated black rice Cempo Ireng variety as a functional ingredient for obesity control. GRAPHICAL ABSTRACT